2019
DOI: 10.1007/s10658-019-01752-9
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses of T-2, HT-2 and DON mycotoxins and Fusarium species in oat to climate, weather, tillage and cereal intensity

Abstract: Analysis of survey data from 804 spring-oat fields divided into five climatic regions suggested that low inoculum level of Fusarium langsethiae was a major limiter of T-2 + HT-2. A 30-year climate with a cool and rainy 10-day period preceding estimated mid-anthesis and a warm 3-week period following anthesis were positively associated with T-2 + HT-2 contamination. In 12 survey years, warm weather from 4 weeks before GS65 until harvesting increased T-2 + HT-2, except in the 1-2 weeks preceding mid-anthesis, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 56 publications
(83 reference statements)
8
30
0
Order By: Relevance
“…Moderate to high mycotoxin levels in unsorted grain samples were detected for HT2+T2 toxins and EnnB in 2015, and DON in 2018 ( Figure 2). Similar contrasting occurrences of HT2+T2 vs. DON in oats have been reported in other studies [9,29,30]. The mycotoxin levels in samples of unsorted grain of the remaining mycotoxins, i.e., ADON, NIV, EnnA, EnnA1, EnnB1, BEA and ZEA were generally low in samples from both years.…”
Section: Mycotoxin Content In the Oat Grain Lotssupporting
confidence: 87%
“…Moderate to high mycotoxin levels in unsorted grain samples were detected for HT2+T2 toxins and EnnB in 2015, and DON in 2018 ( Figure 2). Similar contrasting occurrences of HT2+T2 vs. DON in oats have been reported in other studies [9,29,30]. The mycotoxin levels in samples of unsorted grain of the remaining mycotoxins, i.e., ADON, NIV, EnnA, EnnA1, EnnB1, BEA and ZEA were generally low in samples from both years.…”
Section: Mycotoxin Content In the Oat Grain Lotssupporting
confidence: 87%
“…Non-inversion management decreased the occurrence of the toxins forming pathogens F. culmorum and F. graminearum whereas the predominantly saprophytic species F. avenaceum was detected more often (Figures 2A,B and Supplementary Table S2). On barley monoculture, F. graminearum was the main mycotoxin DON producer (Kaukoranta et al, 2019) in grain (harvested and dried) and stubble (collected and analyzed in September) under plowing. The toxins forming pathogen F. culmorum was the test fungus for the fungistasis surface assay (see section "Fungistasis Surface Bioassay").…”
Section: Prevalence Of Soil-borne Fusarium Spp In the Field And Cropmentioning
confidence: 99%
“…to infect cereals. However, recently, Kaukoranta et al (2019) concluded from a large survey data of 804 spring-oat fields in Finland that Fusarium spp., especially pathogenic F. culmorum, tended to be more common under plowing than under non-inversion tillage. In line with this, we found that the predominantly saprophytic F. avenaceum was more abundant under noninversion practice, whereas the opposite was true for the pathogenic ones.…”
Section: Soil Fungistasis and Prevalence Of Soil-borne Fusarium Culmomentioning
confidence: 99%
“…Early maturation may partly explain why 'BOR31' was less susceptible in the field than in the greenhouse. Late maturing oats are more likely to face moister autumn weather, which can promote the accumulation of DON toxins especially when they are suitably timed with the right temperature (Hjelkrem et al 2017, Kaukoranta et al 2019. However, again the breeding line 'BOR03' is an outlier in Table 4 and an example of an oat with good mycotoxin resistance combined with late maturity.…”
Section: The Role Of Passive Resistance Mechanismsmentioning
confidence: 99%
“…Moreover, the mycotoxin accumulation is also dependent on particular species causing the FHB. Natural infections are often highly dependent on factors such as the weather (Hjelkrem et al 2017), the previous crop (Dill-Macky and Jones 2000) and the tillage (Kaukoranta et al 2019). In wheat, the disease severity can be used as a parameter for selection (Buerstmayr and Lemmens 2015), but this is not seen as a reliable method for oats and therefore more analyses are needed from harvested samples (Tekle et al 2018).…”
Section: Introductionmentioning
confidence: 99%